Getting your publication right – Part 3 structuring a research manuscript: A guide to writing clinical trials - Aditya Mitra; R. S. Mohan Kumar; Shishir Singh; Velmurugan Natanasabapathy; Sonali Sharma; Geeta Asthana; Sonali Taneja; Suparna Ganguly Saha (Journal of Conservative Dentistry and Endodontics, 2026)
Abstract Clinical trials form the cornerstone of evidence-based healthcare and play a crucial role in translating research into clinical practice. However, successful publication of clinical trials requires not only scientific rigor but also strategic planning, ethical transparency, accurate reporting, and effective scientific writing. This narrative review explores the “art” of publishing clinical trials, highlighting essential components from protocol development to manuscript submission and peer-review navigation. Key aspects discussed include formulation of a focused research question, trial registration, adherence to Consolidated Standards of Reporting Trials guidelines, ethical considerations, statistical reporting, authorship integrity, and journal selection. Common reasons for manuscript rejection and practical approaches to improve acceptance rates are also reviewed. The review further emphasizes the importance of clarity, reproducibility, data presentation, and avoidance of publication bias. By integrating methodological standards with effective communication skills, researchers can enhance the quality, visibility, and impact of their clinical trial publications. This review aims to guide clinicians, academicians, and early-career researchers in preparing scientifically robust and publishable clinical trial manuscripts.